Moringa leaves for anemia treatment among teenagers - Rahmawati, Nur; Mareta, Reni; Subrata, Sumarno Adi (Innovation in Health for Society, 2023)
Anemia occurs due to the low levels of hemoglobin and carbon dioxide in the tissues. It is essential to provide comprehensive treatment to avoid the negative impacts of anemia. For example, using herbal therapy for anemia treatment, including moringa leaves. The study aimed to evaluate the use of that leaves in anemia. This research design uses a case study using purposive sampling. This research data was taken using participatory observation, interviews, and documentation. This study's results indicate that applying Moringa leaf extract to increase hemoglobin in adolescent girls can increase hemoglobin levels. Keywords: Teenage girl; hemoglobin; moringa leaf extract; activity intolerance; innovation in health